Relationship between gingival bleeding and blood glucose level: a case-control study - N. Sayeeganesh; P. K. Baskar; B. Manovijay; R Saranyan; N. Shanmugasundaram; N Vijayakumar (International Journal of Medical Research and Review, 2015)
Aim: To correlate the percentage of gingival bleeding sites and blood glucose levels in diabetic and non-diabetic patients.Materials and methods: a total of hundred patients participated in this case-control study. They were grouped in to two groups. Group 1 consisted of 50 type II diabetic patients and group II consisted of 50 non-diabetic patients. Post prandial blood glucose levels oral-hygiene index and percentage of sites with bleeding on probing were recorded. The results obtained were analysed statistically using students‘t’ test.Results: Bleeding tendencies were more in diabetic patients compared to non-diabetic patients.It was found to be highly statistically significant (P<0.01).Conclusion: The study suggested the association of gingival bleeding to the blood glucose level. Blood glucose level reflects their metabolic rates.